Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $b_1 = \left(\begin{matrix}-1 \\ -3\end{matrix}\right)$ and $b_2 = \left(\begin{matrix} -3 \\ -10\end{matrix}\right)$. The set $B = \{b_1, b_2\}$ is a basis for $\mathbb{R}^2$. Let $T: \mathbb{R}^2 \to \mathbb{R}^2$ is a linear transformation such that $T(b_1) = 4b_1 + 4b_2$ and $T(b_2) = 4b_1 + 5b_2$. Then the matrix of $T$ relative to the basis $B$ is

$$[T]_B = \left(\begin{matrix} \color{red}{4} && \color{red}{4} \\ \color{red}{4} && \color{red}{5} \end{matrix}\right),$$

and the matrix of $T$ relative to the standard basis $E$ for $\mathbb{R}^2$ is

$$[T]_E = \left(\begin{matrix} \color{red}{?} && \color{red}{?} \\ \color{red}{?} && \color{red}{?}\end{matrix}\right).$$

I managed to figure out the first part. I think that the standard basis $E$ would be $e_1 = (1,0)$ and $e_2 = (0,1)$ but I don't know how to use this to solve the second half of the question.

share|improve this question
    
Find $a_1, a_2 \in \mathbf R$ such that $a_1b_1 + a_2b_2 = (1, 0)$. You need to make the second coordinate zero, i.e. arrange for $-3a_1 - 10a_2 = 0$. –  Dylan Moreland Mar 26 '12 at 15:24
    
en.wikipedia.org/wiki/Change_of_basis –  Rasmus Mar 26 '12 at 15:25
    
@DylanMoreland I'm not sure that there is an a1 and a2 that meet this requirement... –  StickFigs Mar 26 '12 at 15:39
    
@DylanMoreland Ok I got a1 = {-10,-10} and a2 ={3,3} but these are not the correct answers... –  StickFigs Mar 26 '12 at 15:52

3 Answers 3

up vote 1 down vote accepted

Recall theorem :We know that $[T]_E=P[T]_BP^{-1}$ where $P=[\operatorname{id}]_{E,B}=[b_1 \,\, b_2]$. Now you can easily solve it.

share|improve this answer
    
I get it now! Thank you! –  StickFigs Mar 26 '12 at 16:04

Recall what the matrix $[\, T\,]_B$ is:

If you write a vector $x\in\Bbb R^2$ in terms of the basis $B=\{\,b_1,b_2\,\}$ $$ x=\alpha_1 b_1+\alpha_2 b_2, $$ then if you multiply $[\, T\,]_B$ by the coordinate vector $x_B=\bigl[{\alpha_1\atop\alpha_2}\bigr]$, you get the coordinate vector of $T(x)$ with respect to $B$. That is $$\tag{1} [T(x)]_B = [\,T\,]_B x_B. $$
Now the columns of the matrix $[\,T\,]_E$ where $E=\{e_1,e_2\}$ are the vectors $T(e_1)$ and $T(e_2)$. To find these vectors, we can use the matrix $[\, T\,]_B$. There are three steps involved here. Considering the vector $e_2$, we have to

  1. Find the coordinates of $e_2$ with respect to the basis $B$.
  2. Find the coordinates of $T(e_2)$ with respect to the basis $B$.
  3. Find $T(e_2)$ expressed in the standard basis.

Step 1: For $e_2=(0,1)$, we first find the coordinates of $e_2$ in terms of the basis $B$. Towards this end, we have to solve the system $$ \Bigl[{0\atop1}\Bigr]= \alpha_1 \Bigl[{-1\atop-3}\Bigr] +\alpha_2\Bigl[{-3\atop-10}\Bigr]. $$ Doing so gives: $$\alpha_1=3,\quad \alpha_2=-1$$ The coordinate vector of $e_2$ with respect to $B$ is $\bigl[{3\atop-1}\bigr]$.

Note we could have done this differently: the coordinate vector $\bigl[{\alpha_1\atop\alpha_2}\bigr]$ of $x$ with respect to $B$ satisfies $[b_1 \ b_2] \bigl[{\alpha_1\atop\alpha_2}\bigr] =x$; so $\bigl[{\alpha_1\atop\alpha_2} \bigr]=[b_1 \ b_2]^{-1} x$. Thus we could have found $[b_1\ b_2]^{-1}$ and just multiplied this by $e_2$. This is actually preferable, since we can use the inverse when considering $e_1$ later.


Step 2: Using $(1)$ now, the coordinate vector of $T(e_2)$ with respect to $B$ is $$ [\,T\,]_B (e_2)_B = \Bigl[ \matrix{4&4\cr 4&5 }\Bigr]\Bigl[{3\atop -1} \Bigr] = \Bigl[{8\atop 7} \Bigr]. $$

Step 3: But note that $T(e_2)$ is not the vector $\bigl[{8\atop 7} \bigr]$; this vector gives the coordinates of $T(e_2)$ with respect to the basis $B$. In general, if $x_B$ is the coordinate vector of $x$ with respect to $B$, then $x=[b_1\ b_2] x_B$; so $$ T(e_2)=[b_1\ b_2]\Bigl[{8\atop 7} \Bigr] =8\, b_1+7\, b_2= 8\Bigl[{-1\atop -3} \Bigr] +7 \Bigl[{-3\atop -10} \Bigr] =\Bigl[{-29\atop -94} \Bigr]. $$


Thus, the second column of $[\,T\,]_E$ is $\bigl[{-29\atop -94} \bigr]$.

To find the first column of $[\,T\,]_E$, apply the same procedure to the vector $e_1$. The first step here would be to write $e_1$ in terms of the basis $B$. To do that, you need to solve the system $$ \Bigl[{1\atop0}\Bigr]= \alpha_1 \Bigl[{-1\atop-3}\Bigr] +\alpha_2\Bigl[{-3\atop-10}\Bigr]. $$ or compute: $$\Bigl[{\alpha_1\atop\alpha_2} \Bigr]=[b_1 \ b_2]^{-1} e_1.$$



In general, given $x$ written in terms of the standard basis, the coordinates of $x$ with respect to $B$ are given by $ P^{-1} x$ where $P=[b_1\ b_2]$. Then the coordinates of $T(x)$ with respect to $B$ are $[\,T\,]_B P^{-1} x$. Then we have that $T(x)$ expressed in terms of the usual basis is $P [\,T\,]_B P^{-1} x$. So, $$ [\,T\,]_E = P[\,T\,]_B P^{-1}. $$

share|improve this answer

Let's think about this.

Well we need the values of $T(e_1), T(e_2)$ in terms of $e_1,e_2$.

So first we are going to have to write $b_1, b_2$ in terms of $e_1,e_2$.

If we do this and use it in our definition of $T$ then we see that:

$ -T(e_1) - 3T(e_2) = -16e_1 -52e_2$

$ -3T(e_1) - 10T(e_2) = -19e_1 -62e_2$

We can now solve these equations for $T(e_1), T(e_2)$ and get:

$T(e_1) = 103e_1 +334e_2$

$T(e_2) = -29e_1 - 94e_2$

From this you get the matrix of $T$ with respect to the standard basis.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.